The control of poultry salmonellosis using organic agents: an updated overview - El-Saadony, Mohamed T.; Salem, Heba M.; El-Tahan, Amira M.; Abd El-Mageed, Taia A.; Soliman, Soliman M.; Khafaga, Asmaa F.; Swelum, Ayman A.; Ahmed, Ahmed E.; Alshammari, Fahdah A.; Abd El-Hack, Mohamed E. (Poultry science, 2022)
Salmonellosis is a severe problem that threatens the poultry sector worldwide right now. Salmonella gallinarium and Salmonella pullorum (Fowl typhoid) are the most pathogenic serovars in avian species leading to systemic infection resulting in severe economic losses in the poultry industry. Nontyphoidal serotypes of Salmonella (Paratyphoid disease) constitute a public health hazard for their involvement in food poisoning problems in addition to their zoonotic importance. Also, Salmonella species distribution is particularly extensive. They resisted environmental conditions that made it difficult to control their spread for a long time. Therefore, the current review aimed to through light on Salmonellosis in poultry with particular references to its pathogenesis, economic importance, immune response to Salmonella, Salmonella antibiotics resistance, possible methods for prevention and control of such problems using promising antibiotics alternatives including probiotics, prebiotics, symbiotics, organic acids, essential oils, cinnamaldehyde, chitosan, nanoparticles, and vaccines.